2008
DOI: 10.13001/1081-3810.1260
|View full text |Cite
|
Sign up to set email alerts
|

Group inverses of matrices with path graphs

Abstract: Abstract.A simple formula for the group inverse of a 2 × 2 block matrix with a bipartite digraph is given in terms of the block matrices. This formula is used to give a graph-theoretic description of the group inverse of an irreducible tridiagonal matrix of odd order with zero diagonal (which is singular). Relations between the zero/nonzero structures of the group inverse and the Moore-Penrose inverse of such matrices are given. An extension of the graph-theoretic description of the group inverse to singular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Note that rank CB = 3 > rank CBC = 2 and index CB = 2; thus by Theorem 3.6 or Corollary 3.7, index A = 2s + 1 = 3. Although A # does not exist, (BC) # does exist and thus results in [5] can be applied to determine A D in this example.…”
Section: Theorem 35 Let a Be As In (14) And Suppose That Index Bc mentioning
confidence: 99%
“…Note that rank CB = 3 > rank CBC = 2 and index CB = 2; thus by Theorem 3.6 or Corollary 3.7, index A = 2s + 1 = 3. Although A # does not exist, (BC) # does exist and thus results in [5] can be applied to determine A D in this example.…”
Section: Theorem 35 Let a Be As In (14) And Suppose That Index Bc mentioning
confidence: 99%
“…Indeed, generalized inverses are useful tools in areas such as special matrix theory, singular differential and difference equations and graph theory; see [5], [9] [11], [12] and [15]. For example, in [9] it is shown that the adjacency matrix of a bipartite graph can be written in the form of 0 B C 0 , and necessary and sufficient conditions are given for the existence and representation of the group inverse of a block matrix 0 B C 0 .…”
Section: Introduction Let K Be a Skew Field And Kmentioning
confidence: 99%
“…For a matrix B, let B + denote the Moore-Penrose inverse of B. Some representations for the group inverse of block matrices (operators) are given in [2][3][4][5][6][7][8]11,12,14,16,17,28]. More details for the theory of generalized inverse can be found in [9].…”
Section: It Is Well Known That the Group Inverse Of A Exists If And Omentioning
confidence: 99%